Analisis Wacana Kritis Menggunakan Paradigma Kritis dalam Berita “Wonosalam diguyur Hujan Es, Warga Sempat Panik” Radar Jombang, Jawapos - Hasbullah, Afif; Lestari, Laila Tri; Huda, Khoirul; Ramadhani, Dicky Ardany (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2025)
The researcher uses the critical discourse analysis technique of the Teun Van Dijk model and finds that the news in the Jawa Pos Radar Jombang builds a discourse that in the event of hail, residents need to be vigilant, remembering that this is not the first time this has happened in the Jombang area. The reporter in this news places himself as a second party who gets information directly from the source so that the reality can be accepted by the public as the truth. Researchers find discourse with the help of text analysis, context and social cognition. The researcher found that the discourse built in the Jawa Pos news provides an overview of the situation that occurred at the time of the hail event in the Wonosalam area. Researchers also found that the Jawa Pos news was influenced by the interests of the Jawa Pos daily news.